Cleavage in the gamma-subunit of the epithelial sodium channel (ENaC) plays an important role in the proteolytic activation of near-silent channels - Diyakov, Alexey; Bera, Katarzyna; Mokrushina, Marianna; Krüger, Bettina; Korbmacher, Christoph (The Journal of Physiology, 2008)
The mechanisms by which proteases activate the epithelial sodium channel (ENaC) are not yet fully understood. We investigated the effect of extracellular proteases on rat ENaC heterologously expressed in Xenopus laevi s oocytes. Application of trypsin increased ENaC whole-oocyte currents by about 8-fold without a concomitant increase in channel surface expression. The stimulatory effect of trypsin was preserved in oocytes expressing αγ-ENaC, but was abolished in oocytes expressing αβ-ENaC. Thus, the γ-subunit appears to be essential for channel activation by extracellular proteases. Site-directed mutagenesis of a putative prostasin cleavage site in the extracellular loop of the γ-subunit revealed that mutating the 181Lys residue to alanine (γK181A) increases ENaC baseline whole-oocyte currents, decreases channel surface expression, and largely reduces the stimulatory effect of extracellular proteases (trypsin, chymotrypsin and human neutrophil elastase). In single-channel recordings from outside-out patches we demonstrated that the γK181A mutation essentially abolishes the activation of near-silent channels by trypsin, while a stimulatory effect of trypsin on channel gating is preserved. This apparent dual effect of trypsin on channel gating and on the recruitment of near-silent channels was confirmed by experiments using the β518C mutant ENaC which can be converted to a channel with an open probability of nearly one by exposure to a sulfhydryl reagent. Interestingly, the γK181A mutation results in the spontaneous appearance of a 67 kDa fragment of the γ-subunit in the plasma membrane which can be prevented by a furin inhibitor and also occurs after channel activation by extracellular trypsin. This suggests that the mutation promotes channel cleavage and activation by endogenous proteases. This would lower the pool of near-silent channels and explain the constitutive activation and reduced responsiveness of the mutant channel to extracellular proteases. We conclude that the mutated site (K181A) affects a region in the γ-subunit of ENaC that is functionally important for the activation of near-silent channels by extracellular proteases. © 2008 The Author. Journal compilation © 2008 The Physiological Society.
UnivIS-Import:2015-03-09:Pub.2008.med.IPK.LPVP.cleava